Resistance is fertile: productive responses to student pushback - Martin, Paul (My University, 2017)
When we as faculty members get pushback from students about any kind of innovation, assignment, or teaching choice, we tend to react in a number of different ways. Sometimes we stubbornly carry through with our plan and other times we acquiesce and make changes based on what the students want. In both cases, we often feel resentful or wonder if we’ve done the right thing. In this session, we’ll explore the reasons behind student resistance and how we can place student learning at the heart of how we respond to it.
Presented on September 19 and 20, 2017 at the Centre for the Advancement of Faculty Excellence at MacEwan University in Edmonton, Alberta.
Keywords: learning; teaching; student resistance